Contribution to investigation of behavior of machining center vital elements - Borojev, Ljubomir; Zeljković, Milan; Rekecki, Jožef; Gatalo, Ratko; Andrić, Josip; Šijakov, Vasa (Journal of Production Engineering, 1992)
The paper deals with some results originated in collaboration between the Institute for production engineering and one domestic machine tool producer. These results relate to the development of new solutions of some horizontal machining center elements. So that, the special attention is paid to elements analysis. That .is indispensable for making the best choice of significant machine modules, among all varieties of up-to-date solutions. For having insight into performances and working behavior of realized machine with new modules, some experimental investigation have been performed. A part of obtained results are given in this paper. They are related to static and heat behavior. The static characteristic and stiffness of spindle unit are determined, It has been done for radial and axial direction, loading the spindle nose in both senses. The temperature rise curves for several rotation speeds are defined as well. The results of starting force investigation for two guide types (TURCIT slide ways and STAR roller ways) are given too. Finally, the machining center noise level is presented.